Analysis of real-world PD-L1 IHC 28-8 and 22C3 pharmDx assay utilisation, turnaround times and analytical concordance across multiple tumour types. Issue 10 (26th June 2020) - Krigsfeld, Gabriel S; Prince, Emily A; Pratt, James; Chizhevsky, Vladislav; William Ragheb, Josette; Novotny Jr, James; Huron, David
Abstract : Aims: Programmed death-1/programmed death ligand 1 (PD-1/PD-L1) inhibitor therapy is accompanied by companion or complementary PD-L1 testing in some tumour types. We investigated utilisation of the Dako PD-L1 IHC 28-8 and 22C3 pharmDx assays and the Ventana PD-L1 (SP142) assay and evaluated concordance between the 28-8 and 22C3 assays in a real-world cohort of patients tested at a single US national reference laboratory. Methods: NeoGenomics Laboratories performed PD-L1 testing on tumour samples between October 2015 and March 2018. PD-L1 test results were matched with patient characteristics using unique identifiers. Concordance between the 28-8 and 22C3 assays was evaluated in matched tumour samples. Data were evaluated across multiple tumour types and in subgroups of patients with lung cancer, melanoma, squamous cell carcinoma of the head and neck, and urothelial carcinoma. Results: 62 180 individual PD-L1 tests were conducted on samples from 55 652 patients. PD-L1 test volume increased ~10-fold over the period evaluated. Test failure rates were typically low, and test turnaround time (TAT) ranged between 2 and 4 days. Concordance between the 28-8 and 22C3 assays was strong in the overall population and across tumour type subgroups (Kendall's tau correlations of 0.94 and 0.92–0.98, respectively). Conclusions: Test failure rates for PD-L1 tests were low and TAT remained reasonable despite marked increases in test volume. Concordance was high between the 28-8 and 22C3 assays across a range of tumour types and biopsy locations. These findings add to the literature showing high concordance between the 28-8 and 22C3 assays.